Global Yijing
XXII, 245 p. 57 illus., 1 illus. in color.
Keywords: This book is an examination of the globalization of the Yijing from cross-cultural and comparative perspectives, with a special focus on the Yijing encounters with world religions and thoughts over the past centuries. It presents an ambitious effort to bring together leading Yijing—The Book of Changes—scholars in the world. Composed of three parts and twelve chapters, it begins with a conceptualized narrative of the globalization of the Yijing, highlighting the intercultural encounters and transformation of the Yijing in different religious, philosophical, and cultural traditions across the globe. Part One investigates the interaction of the Yijing in Asian religions and philosophy including the Confucian and Buddhist traditions, as well as Maoism in Japan. Part Two explores how the Yijing was creatively and provocatively interpreted by Jesuit and Protestant missionaries, Chinese Christian intellectuals, and Chinese Islamic scholars from the Qing period to 20th century China. Part Three examines the multifaceted issues associated with the reception and transformation of the Yijing in Western thoughts, like French occultism, Carl Jung’s analytical psychology and John Cage’s experimental music theory and practice. This book is an essential reading for those who are interested in the Yijing and also serves as a useful reference for students and scholars of Chinese culture, Asian philosophy, East Asian studies, and translation studies.